Internalization of athletic body ideal as a mediating variable between family influence and body image of young women. A cross-cultural study of polish, Italian, and Ukrainian women - Izydorczyk, Bernadetta; Głomb, Kaja; Bętkowska-Korpała, Barbara; Yablonska, Tetiana; Bulatevych, Nataliya; Opałka, Renata; Lizińczyk, Sebastian; Sitnik-Warchulska, Katarzyna; Radtke, Bartosz M.; Sajewicz-Radtke, Urszula; Lipowska, Małgorzata (Frontiers in Psychiatry, 2023)
Our aim was to analyse the strength of the family's influence on the internalization of the ideal of an athletic figure and, consequently, on the multifactorial image of the body, from the perspective of intercultural differences. A total of 488 healthy women aged 19-26; of Polish (154), Ukrainian (228), and Italian (106) took part in the study. The Sociocultural Attitudes Towards Appearance Questionnaire (SATAQ-4) and the Multidimensional Body-Self Relations Questionnaire (MBSRQ 69) were used to measure athletic ideal internalization and family pressure. The body image of Ukrainian, Polish and Italian women depends both depends on the degree of internalization the ideal of an athletic figure and influence of the family. The research also suggests significant differences between the three populations, which may suggest cultural differences between young women living in Eastern, Central and South European countries.